Does ex vivo perfusion lead to more or less intimal thickening in the first‐year post–heart transplantation?. Issue 8 (11th July 2019) - Sato, Takuma; Azarbal, Babak; Cheng, Richard; Esmailian, Fardad; Patel, Jignesh; Kittleson, Michelle; Czer, Lawrence; Thottam, Maria; Levine, Ryan; Dimbil, Sadia; Olymbios, Michael; Anzai, Toshihisa; et al.
Abstract: Background: The Organ Care System (OCS), an ex vivo heart perfusion platform, represents an alternative to the current standard of cold organ storage that sustains the donor heart in a near‐physiologic state. Previous reports showed that this system had significantly shortened the cold ischemic time from standard cold storage (CS). However, the effect of reduced ischemic injury against the coronary vascular bed has not been examined by intravascular ultrasound (IVUS). Methods: Between August 2011 and February 2013, heart transplant (HTx) candidates enrolled in the PROCEED 2 trial were randomized to either CS or OCS. IVUS was performed at 4‐6 weeks (baseline) and repeated 1 year after transplantation. The change in maximal intimal thickness (MIT) and other clinical outcomes were examined. Results: Thirty‐nine patients were randomized and underwent HTx by OCS (n=16) or CS (n=18). Of these, 18 patients (OCS: n=5, CS: n=13) with paired IVUS were examined. There were no significant differences in the change of MIT and other clinical outcomes between the groups. Conclusion: The incidence of cardiac allograft vasculopathy in donor hearts preserved with the OCS versus CS was similar. These results suggest that this ex vivo allograft perfusion system is a promising and valid platform for donor heart transportation.